x+7=-3+3x

Simple and best practice solution for x+7=-3+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+7=-3+3x equation:


Simplifying
x + 7 = -3 + 3x

Reorder the terms:
7 + x = -3 + 3x

Solving
7 + x = -3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
7 + x + -3x = -3 + 3x + -3x

Combine like terms: x + -3x = -2x
7 + -2x = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
7 + -2x = -3 + 0
7 + -2x = -3

Add '-7' to each side of the equation.
7 + -7 + -2x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + -2x = -3 + -7
-2x = -3 + -7

Combine like terms: -3 + -7 = -10
-2x = -10

Divide each side by '-2'.
x = 5

Simplifying
x = 5

See similar equations:

| .60x+.30(90)=.50(x+90) | | 6=18b | | 3x+15=12b-3b | | x*-5=10 | | 16t^2-128+400=0 | | 2a+24-3a=5a | | 8p-4=7p-2 | | n^2-34n-251=0 | | t^2-8+25=0 | | 1-m=1-m | | 16.28+8=100 | | -4n+2=-13-7n | | x^7-5x+6=0 | | 13x+23y=-5 | | -6+4p=5p-4 | | -3+2x-9=9 | | -10(3+2)-7= | | 569.7844=3135.6289h | | v+4=3v-6 | | 2=-2x+25 | | -7x=-16 | | 12+x-2x=-4+x | | 5s-11=13+s | | f(x+7)=x^2+8x+5 | | -7-7x=-16 | | 12x+6=x | | 5v-2=2+2v-2+1 | | -18=-2+2w | | 6n-7=n+3 | | 2m+11=33 | | .40x+0.06(30)=9.8 | | -8+x+3x=-8+4x |

Equations solver categories